2435. Clinical Outcomes With Ceftolozane–Tazobactam in Patients With Multidrug-Resistant (MDR) Pseudomonas aeruginosa Bloodstream Infections: A Multi-Center Study. (26th November 2018) - King, Madeline; Elabor, Abdulrahman; Molnar, Esther; Gallagher, Jason; ,
Abstract: Background: Ceftolozane-tazobactam (TOL-TAZ) is a novel cephalosporin combination that is beneficial for the treatment of multidrug-resistant (MDR) Pseudomonas infections. However, little data are available on the utility of TOL-TAZ for patients with bloodstream infections (BSIs) caused by this organism. Methods: A retrospective, multicenter chart review was conducted at 11 hospitals to evaluate the utility of TOL-TAZ for MDR Pseudomonas BSIs from June 2016 to February 2018. Patients were included if they were over 18 years old with positive blood cultures for Pseudomonas aeruginosa and received TOL-TAZ for at least 24 hours. Patients were evaluated for in-hospital and 30-day mortality, as well as microbiologic and clinical cure. Results: Conclusion: In this multi-center evaluation of 25 patients from 11 health centers, mortality was seen at 30 days and at the end of stay in 28% and 24% of patients, respectively. Clinical and microbiologic success occurred in over 70% of patients. One patient developed C. difficile infection. The 7 patients with primary bacteremia had microbiologic success and survived their hospital stay. Two of 3 patients with pneumonia who survived received high dose TOL-TAZ. TOL-TAZ is an option for patients with MDR Pseudomonas bloodstream infections. Disclosures: J. Gallagher, Achaogen: Consultant, Consulting fee. Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee and Research grant. Allergan: Consultant and Speaker's Bureau, Consulting fee. Astellas: Consultant and Speaker's Bureau, Consulting fee. Cempra: Consultant, Consulting fee. Cidara: Consultant, Consulting fee. CutisPharma: Consultant, Consulting fee. Paratek: Consultant, Consulting fee. Shionogi: Consultant, Consulting fee. Tetraphase: Consultant, Consulting fee. Theravance: Consultant, Consulting fee. The Medicines Company: Consultant, Consulting fee. Melinta: Speaker's Bureau, Consulting fee.